PERAN PENTING AKUNTANSI FORENSIK DAN AUDIT INVESTIGATIF DALAM UPAYA PENCEGAHAN DAN PENGUNGKAPAN FRAUD - Ika Sulistiani; Octavia Pramudyastuti (Fakultas Ekonomi Universitas Pekalongan, 2021)
Fraud is not a new disease in the world economy. This crime has even resulted in a tremendous loss to a company, country, and world. According to ACFE, every year the organization loss of gross income reaches 5% due to fraud. Therefore, prevention and disclosure measures are also essential to deal with this serious problem. One of them is using forensic accounting and investigative auditing. However, as a new discipline, only a few people understand forensic accounting and investigative auditing, they still wonder about fraud, nor do they know the techniques for preventing and disclosing fraud. This qualitative research with a literature study approach and uses secondary data to understand the matter. Forensic accounting combines accounting, auditing, and legal knowledge to help resolve legal issues both inside and outside the court. While investigative auditing intends to seek, find, and disclose evidence of the presence or absence of an act of fraud. Fraud can be prevented by implementing adequate internal controls. Then to reveal the existing fraud can be done by following the money technique, using computer forensics, whistleblowing system, or other methods